Efektivitas Terapi Dzikir Dan Teknik Relaksasi Nafas Dalam Terhadap Kecemasan Pasien Appendictomy Usia Remaja - Cikal Bulan Tisna; Wulan Noviani; Eko Susanto (Jurnal Medika Nusantara, 2025)
Appendicitis is an inflammation of the appendix that often requires a surgical removal called an appendectomy. Anxiety is commonly experienced by adolescents facing appendicitis surgery, which can affect their recovery process. Dhikr therapy and deep breathing relaxation techniques are non-pharmacological methods aimed at reducing anxiety levels and providing a sense of calm to patients. This study used a case study approach with one intervention patient and one control patient. Nursing care was provided to adolescent patients with appendicitis who experienced anxiety before undergoing an appendectomy. The intervention consisted of dhikr therapy and deep breathing relaxation techniques administered for 45 minutes. Patient assessment was conducted using the HARS questionnaire and evaluating the patient's vital signs. The study showed a significant reduction in anxiety levels in the adolescent intervention respondent compared to the control respondent. Anxiety scores in the intervention respondents decreased significantly after receiving dhikr therapy and deep breathing relaxation techniques. This indicates that the combination of these two therapies is effective in reducing anxiety in adolescents with appendicitis undergoing an appendectomy. This study concludes that dhikr therapy and deep breathing relaxation techniques can be effective methods for managing anxiety in adolescents facing appendicitis surgery. Implementing these methods in clinical care can help improve the quality of life and recovery process for patients. Further research is recommended to explore the long-term effects of these therapies and their application to a broader population.